Spatial Characterization of Multiple Pulses, With Different Spatial Profiles, From a Single Camera Snapshot - Ariel Veler; Michael Birk; Caleb Dobias; Rodrigo Amezcua Correa; Pavel Sidorenko; Oren Cohen (IEEE Photonics Journal, 2024)
We used a single-shot ptychographic microscope to image the complex-valued (intensity and phase) spatial profiles of multiple ultrashort pulses. Specifically, we present a characterization of a burst of three ultrashort pulses with three nanoseconds delays between pulses using data recorded by a single camera exposure with millisecond integration time. This scheme is promising for various applications, including characterizing spatiotemporal mode-locked or Q-switched lasers, potentially shedding light on their buildup dynamics.